1986
DOI: 10.1128/jb.165.3.1019-1022.1986
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of citric acid accumulation by manganese ions in Aspergillus niger mutants with reduced citrate control of phosphofructokinase

Abstract: Mutant strains of Aspergillus niger with reduced citrate control of carbohydrate catabolism (cic mutants) grow faster than the parent strain on media containing 5% (wt/vol) citrate. The mutants tolerated a higher intracellular citrate concentration than the parent strain. One mutant (cic-713) contained phosphofructokinase activity significantly less sensitive towards citrate than the enzyme from the parent strain. When this mutant was grown under citrate-accumulating conditions, acidogenesis was far less sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Although proteases are normally strictly compartmentalised in the cells and are activated from their pre-pro forms only in the vacuoles, some leakage through the tonoplast into the cytosol must occur, since cleavage of the native Pfk1 enzyme takes place. In A. niger cells, increased protein degradation occurs under Mn 2+ -deficient conditions, which was also reflected by increased intracellular proteinase activities (Ma et al 1985;Schreferl et al 1986). For efficient citric acid fermentation, lack of trace metal ions, particularly Mn 2+ from the medium, is of major importance.…”
Section: Hexokinase and Glucokinasementioning
confidence: 97%
See 1 more Smart Citation
“…Although proteases are normally strictly compartmentalised in the cells and are activated from their pre-pro forms only in the vacuoles, some leakage through the tonoplast into the cytosol must occur, since cleavage of the native Pfk1 enzyme takes place. In A. niger cells, increased protein degradation occurs under Mn 2+ -deficient conditions, which was also reflected by increased intracellular proteinase activities (Ma et al 1985;Schreferl et al 1986). For efficient citric acid fermentation, lack of trace metal ions, particularly Mn 2+ from the medium, is of major importance.…”
Section: Hexokinase and Glucokinasementioning
confidence: 97%
“…Six organic allosteric ligands either increase or decrease substrate binding affinity and concomitantly determine overall enzyme activity (Poorman et al 1984). Pfk1 from A. niger cells was a subject of various studies (Habison et al 1983;Schreferl et al 1986;Arts et al 1987;Legiša and Benčina 1994;Mesojednik and Legiša 2005;Mlakar and Legiša 2006). The enzyme attracted the interest of investigators, due to its ability to maintain a high glycolytic flux in spite of elevated intracellular concentrations of citrate, a well-known inhibitor of Pfk1, which was reported to reach concentrations between 4 mM (Rö hr and Kubicek 1981) and 10 mM (Legiša and Kidrič 1989).…”
Section: Hexokinase and Glucokinasementioning
confidence: 99%
“…Much has been reported on PFK1 characteristics from the filamentous fungus A. niger in the past (1,5,6,17,20,27). The enzyme attracted the interest of investigators, due to its ability to maintain a high glycolytic flux in spite of elevated intracellular concentrations of citrate during the process of the secretion of citric acid, which was reported to reach a concentration between 4 mM (23) and 7 mM (13).…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory properties of PFK1 attracted the interest of investigators in order to explain the phenomenon (1, 5, 6), since this enzyme was shown to be a major control point of A. niger glycolysis (19,27). By studying the kinetics on a partially purified enzyme, it was proposed that the citrate inhibition of PFK1 was counteracted by NH 4 ϩ ions and AMP in A. niger cells (5, 6), while fructose-2,6-bisphosphate significantly stimulated the activity of the enzyme and relieved the inhibition caused by ATP (1).…”
mentioning
confidence: 99%
“…3). The effects of Mn 2ϩ concentration on citric acid production have been reported previously (21,44,45), but in the present study, the effects of Mn 2ϩ on A. niger morphology and citric acid production were examined concurrently. Low Mn 2ϩ concentrations (10 to 13 ppb) also significantly suppressed the biomass accumulation (data not shown).…”
Section: Fig 2 Effects Of Mn 2ϩ Onmentioning
confidence: 97%